2022
DOI: 10.1021/acsnano.2c06275
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Stimulation Using 3D Wireframe DNA Origami

Abstract: Three-dimensional wireframe DNA origami have programmable structural and sequence features that render them potentially suitable for prophylactic and therapeutic applications. However, their innate immunological properties, which stem from parameters including geometric shape and cytosine-phosphate-guanine dinucleotide (CpG) content, remain largely unknown. Here, we investigate the immunostimulatory properties of 3D wireframe DNA origami on the TLR9 pathway using both reporter cell lines and primary immune cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 70 publications
2
43
0
Order By: Relevance
“…We note that for some applications, such as cancer immunotherapy, the ability to stimulate proinflammatory cytokine induction might be a preferable characteristic of a delivery vehicle. Researchers have demonstrated proof-of-concepts that immune system stimulation can be programmed with NANPs. ,,, We anticipate this capability will be advantageous in future biomedical applications.…”
Section: Discussionmentioning
confidence: 99%
“…We note that for some applications, such as cancer immunotherapy, the ability to stimulate proinflammatory cytokine induction might be a preferable characteristic of a delivery vehicle. Researchers have demonstrated proof-of-concepts that immune system stimulation can be programmed with NANPs. ,,, We anticipate this capability will be advantageous in future biomedical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Independent control over the size and geometry of NANPs with site-specific functionalization may improve tissue- and cell-specific targeting 16 , and their sequence-based programmability can be leveraged for logic-gated, controlled cargo release 17, 18 . NANPs have tunable biodegradation profiles 19 , and can be modified chemically and structurally to control immunostimulation 4, 20, 21 . Additionally, NANPs can simply incorporate combinatorial ratios of nucleic acid therapeutics including siRNAs and CRISPR-RNPs through nucleic acid hybridization 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Initial in vitro cell-based studies revealed context-dependent immunostimulation with examples of rod-like DNA origami being immunologically inert 49 , contrasted by modest immune cell activation by rod-like 20 and wireframe DNA origami 21,50 . Both TLR9 and the cGAS-STING pathways contributed to immune recognition 20, 21 . Additionally, immunostimulation can intentionally be enhanced by the multivalent display of specific immunostimulatory nucleic acids, both in vitro 21, 49 and in vivo 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). In addition, recent studies have shown that DNA origami and particularly the pentagonal bipyramid have negligible immunogenicity, especially in regards to the stimulation of the TLR9 pathway, which is important to determine the specificity of the vaccine response induced by the antigens 43,44 . Therefore, we used the PB structure to present the RBD antigen in a trimeric form, along with multiple CpG ODN 1018 (cytosine-phosphorothioate-guanine oligodeoxynucleotides) adjuvants (Fig.…”
mentioning
confidence: 99%